Effect of Addition of Colloidal Silica to Films of Polyimide, Polyvinylpyridine, Polystyrene, and Polymethylmethacrylate Nano-Composites - Abdalla, Soliman (Materials (Basel), 2016)
Nano-composite films have been the subject of extensive work for developing the energy-storage efficiency of electrostatic capacitors. Factors such as polymer purity, nanoparticle size, and film morphology drastically affect the electrostatic efficiency of the dielectric material that forms the insulating film between the conductive electrodes of a capacitor. This in turn affects the energy storage performance of the capacitor. In the present work, we have studied the dielectric properties of four highly pure amorphous polymer films: polymethyl methacrylate (PMMA), polystyrene, polyimide and poly-4-vinylpyridine. Comparison between the dielectric properties of these polymers has revealed that the higher breakdown performance is a character of polyimide (PI) and PMMA. Also, our experimental data shows that adding colloidal silica to PMMA and PI leads to a net decrease in the dielectric properties compared to the pure polymer.